En jämförelse av hästens allmäntillstånd efter första respektive revaccination med EHV vaccin - Gustafsson, Isabella (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2019)
Equine herpesvirus (EHV) is a common virus in horse populations around the world. The condition is counted as a notifiable disease in Sweden. There are currently nine different types. EHV-1,4 are the two most common types causing diseases in horses. The condition causes respiratory infections, abortion and/or neurological disease. The virus is primarily an airborne infection and is spread through droplet infections. Symptoms by EHV can be fever, decreased appetite, tiredness, coughing, abnormal breathing sounds, swelling in the limbs and ataxic in horse’s hind legs. Today there is one vaccine available in Sweden against EHV-1,4.